Managerial Entrepreneurial Competencies Framework for Technical College Programs: Concept and Relevance - Muhammad, AbuBakar Ibrahim; Kamin, Yusri; Abd. Wahid, Nur Husna; Subari, Kamalularifin; Suhairom, Nornazira; Saud, Muhammad Sukri; Suyitno, Suyitno (Journal of Technical Education and Training, 2023)
One of the challenges of technical education in Sub-Saharan Africa, including Nigeria, is the lack of an appropriate entrepreneurial framework for the content of the technical college curriculum. The purpose of this study was to explore the managerial entrepreneurial competencies for technical college programs in Nigeria. This study was guided by a qualitative approach through document analysis and semi-structured interviews with 15 participants selected purposively and 11 Journal Articles were analysed. The empirical findings from semi-structured interviews confirm the theoretical findings in document analysis. This study found several managerial entrepreneurial competencies in document analysis and interviews, eventually analysed thematically. Themes include Business planning, Decision-making, Technical know-how, Interpersonal relationships and Communication. The study analysed only 11 documents and conducted 15 interviews, so the conclusions drawn from these sources depend on the authenticity of the information provided by the participants.  The findings of the study indicate that managerial entrepreneurial competencies are worthy of inclusion in the technical college curriculum in Nigeria. Therefore, it is recommended that the curriculum needs to be reviewed to ensure that it meets the educational changes such as global trends and 21st-century education policies which now become a worldwide phenomenon.